Adenoides sinensis, a new sand-dwelling dinoflagellate species from China and reexamination of Adenoides eludens from an Atlantic strain. Issue 2 (1st March 2018) - Gu, Haifeng; Li, Xintian; Chomérat, Nicolas; Luo, Zhaohe; Sarno, Diana; Gourvil, Priscilla; Balzano, Sergio; Siano, Raffaele
Abstract: The sand-dwelling dinoflagellate genera Adenoides and Pseudadenoides are morphologically very close but distinct in their molecular phylogeny. We established three cultures by isolating single cells from sand samples collected in intertidal zones of Qingdao (Yellow Sea), Dongshan (South China Sea) and Brittany (English Channel, North Atlantic, France). Strain morphology was examined with light and scanning electron microscopy, and both large subunit ribosomal DNA (LSU rDNA) and small subunit ribosomal DNA (SSU rDNA) sequences were amplified. Molecular phylogeny, corroborated by morphological examination showing the existence of a ventral pore, confirmed the identification of the French strain (RCC1982) as Adenoides eludens . The Chinese strains differed from Adenoides eludens in two additional posterior intercalary plates and differed from Pseudadenoides in one additional apical plate having the plate formula of Po, Cp, X, 5′, 6′′, 4S, 5′′′, 5p, 1′′′′ or alternatively Po, Cp, X, 5′, 6′′, 5S, 5′′′, 3p, 2′′′′. Maximum likelihood and Bayesian inference, carried out with concatenated LSU and SSU sequences, demonstrated that the Chinese strains were closely related but different from A. eludens and, in corroboration with morphological evidence, supported their classification as a distinct species, Adenoides sinensis sp. nov . Morphological and molecular results confirmed the close relationship between the two genera Adenoides and Pseudadenoides .